Diagnostic value of recombinant Tp0821 protein in serodiagnosis for syphilis. (April 2016) - Xie, Y.; Xu, M.; Wang, C.; Xiao, J.; Xiao, Y.; Jiang, C.; You, X.; Zhao, F.; Zeng, T.; Liu, S.; Kuang, X.; Wu, Y.
Abstract: Syphilis is a multistage sexually transmitted disease that remains a serious public health concern worldwide. The coexistence of Treponema pallidum with other closely related members of spirochaeta, such as Leptospira spp. and Borrelia burgdorferi, has complicated the serodiagnosis due to cross‐reactive antigens. In this study, recombinant Tp0821 protein was expressed in Escherichia coli and purified by metal affinity chromatography. Then enzyme‐linked immunosorbent assays (ELISAs) based on Tp0821 for the detection of specific antibodies were established. The relative positive rates of the IgM ELISA and the IgG ELISA were found to be 91·0 and 98·3%, respectively, when screening 578 syphilis specimens. The specificities were 94·3 and 100%, respectively, when cross‐checking with serum samples obtained from 30 patients with Lyme disease, five patients with leptospirosis, and 52 uninfected controls. In addition, relative positive rates and specificities of Tp0821 for human sera were all 100% in Western blotting. When compared to the syphilis diagnostic tests commonly used in clinical settings, we found that the results of Tp0821‐based ELISAs correlated well with the results of the treponemal tests, specifically the T . pallidum particle agglutination (TP‐PA) test and the chemiluminescent immunoassay (CIA). Thus, these findings identify Tp0821 as a novel serodiagnostic candidate for syphilis. Significance and Impact of the Study: In this study, we expressed and purified the Treponema pallidum protein Tp0821 and developed Tp0821‐based enzyme‐linked immunosorbent assays (ELISAs) for the detection of specific antibodies. The serodiagnostic performance of the recombinant protein was then evaluated. When compared to the results of syphilis diagnostic tests commonly used in clinical settings, we found that the reactivities of syphilitic sera with the recombinant antigen correlated well with the results of the treponemal tests, specifically the T . pallidum particle agglutination (TP‐PA) test and the chemiluminescent immunoassay (CIA). Thus, the recombinant protein shows promise as a new diagnostic antigen in the ELISAs. Abstract : Significance and Impact of the Study : In this study, we expressed and purified the Treponema pallidum protein Tp0821 and developed Tp0821‐based enzyme‐linked immunosorbent assays (ELISAs) for the detection of specific antibodies. The serodiagnostic performance of the recombinant protein was then evaluated. When compared to the results of syphilis diagnostic tests commonly used in clinical settings, we found that the reactivities of syphilitic sera with the recombinant antigen correlated well with the results of the treponemal tests, specifically the T . pallidum particle agglutination (TP‐PA) test and the chemiluminescent immunoassay (CIA). Thus, the recombinant protein shows promise as a new diagnostic antigen in the ELISAs.